Nexuses between international trade, renewable energy, and transport services: Leading toward practical implications and trade policies - Yu, Zhang; Khan, Abdul Rehman; Thomas, George; Jameel, Kiran; Tanveer, Muhammad; Janjua, Laeeq (Frontiers in Environmental Science, 2022)
This research aims to investigate the connection between logistic indicators, trade, renewable energy, and ICT on transport services in selected 33 developed European countries. The researchers used panel data from 33 developed European countries to test the hypothesis. Panel GMM is an optimal modeling choice in this study from data sets ranging from 2007 to 2020. The results revealed that transport services have a significant positive relationship with Trade, Renewable energy, ICT, and internet usage. Also, the logistic indicators have a significant positive connection with transport services. Further, renewable energy and transport services have a significant positive association with transport services. ICT adoption positively affects road freight transport by enhancing operations' safety, suitability, visibility, and accountability. The effectiveness of these indicators is considerably affected by transport flow predictions and resource allocation strategy. Moreover, the management of high-quality operations requires optimization, and using transport and logistics management systems for transportation services makes it feasible to get optimal outcomes.